2009
DOI: 10.1021/la8037523
|View full text |Cite
|
Sign up to set email alerts
|

Protein Adsorption on Poly(N-vinylpyrrolidone)-Modified Silicon Surfaces Prepared by Surface-Initiated Atom Transfer Radical Polymerization

Abstract: Well-controlled poly(N-vinylpyrrolidone) (PVP)-grafted silicon surfaces were prepared by surface-initiated atom transfer radical polymerization (SI-ATRP) with 1,4-dioxane/water mixtures as solvents and CuCl/5,7,7,12,14,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane (Me6TATD) as a catalyst. The thickness of the PVP layer on the surface increased with reaction time, suggesting that the ATRP grafting of N-vinylpyrrolidone (NVP) from the silicon surfaces was a well-controlled process. The water contact angle and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(95 citation statements)
references
References 43 publications
8
87
0
Order By: Relevance
“…Very recently, we prepared wellcontrolled poly(N-vinylpyrrolidone) (PVP)-grafted silicon surfaces for the first time using SI-ATRP. [26] It was found that surfaces with thick grafted layers showed a dramatic reduction in the level of adsorption of three model proteins (fibrinogen, human serum albumin, and lysozyme) with varying properties. As the thickness of the PVP layer increased, the water contact angle (WCA) gradually decreased and then remained constant beyond a ''critical'' thickness of $13 nm.…”
Section: Hydrophilic Polymers For Surface Modification To Repel Proteinsmentioning
confidence: 99%
“…Very recently, we prepared wellcontrolled poly(N-vinylpyrrolidone) (PVP)-grafted silicon surfaces for the first time using SI-ATRP. [26] It was found that surfaces with thick grafted layers showed a dramatic reduction in the level of adsorption of three model proteins (fibrinogen, human serum albumin, and lysozyme) with varying properties. As the thickness of the PVP layer increased, the water contact angle (WCA) gradually decreased and then remained constant beyond a ''critical'' thickness of $13 nm.…”
Section: Hydrophilic Polymers For Surface Modification To Repel Proteinsmentioning
confidence: 99%
“…11 Recently, it was reported that the capability of PVP to prevent protein adsorption was correlated with its coating and molecule weight. 13,14 It was found that the nanoparticles coated by PVP, with molecular weight of 2,500 and 4,800 Da, were rapidly removed from blood due to complement components and immunoglobulins adsorption. 14 In this report, we loaded UA into poly(N-vinylpyrrolidone)-block-poly (Δ-caprolactone) (PVP-b-PCL) nanoparticles and performed physiochemical characterization.…”
mentioning
confidence: 99%
“…Examples include modification by silane (e.g. PEG-silane or silane with fluorinated groups) and polyelectrolyte multilayers (PEMs) that can be used to modulate hydrophobicity, charge and to add biological specificity to surfaces [19]. For multiphase droplet generation, channel surface properties differ at different stages of droplet synthesis, depending on the continuous phase at different positions in the chip, while for singlephase droplet systems typically the continuous phase does not change and a uniform surface chemistry is used along the channel [20,21].…”
Section: Technical Aspects Of Droplet Engineeringmentioning
confidence: 99%